Connected canine health: Perception and acceptance of wearable technology in Guayaquil, Ecuador - Soriano Tomalá, Karen Lissette; Salazar Mazamba, María de Lourdes; Mieles Soriano, Gloria Fabiola (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2025)
Wearable technology includes smart devices such as collars and sensors that monitor pets' health and activity. This allows for constant interaction between owners, veterinarians, and pets, enabling the detection of health problems and improving animal welfare with data accessible through apps. This research analyzes the perception and acceptance of this technology for monitoring the health of dogs in Guayaquil. The study used a mixed-method approach with 210 dog owners and applied a validated questionnaire to measure opinions. The data were evaluated using SPSS and Excel software. The results show that 51.62 % of participants had a neutral attitude toward their knowledge of the technology. In addition, 55.77 % agreed with factors such as cost and accessibility, and training is recommended to encourage the adoption of these devices.
Keywords: Animal welfare; artificial intelligence; monitoring; canine health; wearables